Addressing Waste Growth Challenges through Collaborative Urban Governance and Local Democratic Engagement in Batam City's - Sari, Cindy Fatika; Lodan, Karol Teovani (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2024)
This abstract explores the challenges and opportunities in solid waste management through waste banks in Batam City, emphasizing the necessity for collaborative efforts among government, industry, and society. The discussion highlights current initiatives and the obstacles encountered in implementing effective waste management practices, particularly focusing on the fragmented nature of existing collaborations and the persistent community behaviors that hinder progress. Key challenges include low environmental awareness, limited community participation in waste sorting, inadequate infrastructure, and inconsistent enforcement of regulations. These issues underscore the need for intensified education, awareness building, and incentivization to foster greater community engagement. The abstract proposes solutions through enhanced collaboration and joint commitment among stakeholders. It advocates for strengthened regulatory frameworks, improved coordination among government agencies, and greater corporate responsibility in prioritizing sustainability. These measures aim to establish a comprehensive waste management system that not only enhances environmental quality but also supports sustainable economic development in Batam City. Ultimately, by addressing these challenges and leveraging collaborative governance, Batam City can achieve a cleaner, healthier environment and sustainable growth for its residents.